The Representativeness of Olea Pollen from Olive Groves and the Late Holocene Landscape Reconstruction in Central Mediterranean - Florenzano, Assunta; Mercuri, Anna Maria; Rinaldi, Rossella; Rattighieri, Eleonora; Fornaciari, Rita; Messora, Rita; Arru, Laura (Frontiers in Earth Science, 2017)
Modern pollen spectra are an invaluable reference tool for paleoenvironmental and cultural landscape reconstructions, but the importance of knowing the pollen rain released from orchards remains underexplored. In particular, the role of cultivated trees is in past and current agrarian landscapes has not been fully investigated. Here, we present a pollen analysis of 70 surface soil samples taken from 12 olive groves in Basilicata and Tuscany, two regions of Italy that exemplify this cultivation in the Mediterranean basin. This study was carried out to assess the representativeness of Olea pollen in modern cultivations. Although many variables can influence the amount of pollen observed in soils, it was clear that most of the pollen was deposited below the trees in the olive groves. A rapid decline in the olive pollen percentages (c. 85% on average) was found when comparing samples taken from IN vs. OUT of each grove. The mean percentages of Olea pollen obtained from the archeological sites close to the studied orchards suggest that olive groves were established far from the Roman farmhouses of Tuscany. Further south, in the core of the Mediterranean basin, the cultivation of Olea trees was likely situated 500–1,000 m from the rural sites in Basilicata, and dated from the Hellenistic to the Medieval period.